Evaluation of drug-induced changes in myocardial repolarisation using the paced evoked response. Issue 4 (October 1982) - Donaldson, R M; Rickards, A F
Abstract : The use of the pace evoked response system in the assessment of drug-induced changes in myocardial repolarisation is reported. Using a conventional pacing electrode lead for both pacing and sensing, this system records the dominantly local repolarisation which follows a controlled (paced) depolarisation from the same site. Measurements of the latency of the ventricular evoked response at matched heart rates before and after drug administration permit the accurate direct comparison of the effects of drugs with class 3 mode of action on cardiac muscle repolarisation. Using this method we have evaluated the effect on the timing of the evoked T wave of two drugs which are known to prolong phase 2 of the action potential. Intravenous amiodarone (5 mg/kg) prolonged the stimulus-peak evoked T wave interval by an average of 39-4 ms (15% of control values); three hours after oral bethanidine (2 mg/kg) this interval increased by an average of 25.8 ms (10% of control values). The effect of therapeutic interventions on the latency of the local paced evoked response provides a simple, accurate assessment of their effect on the cellular action potential duration and constitutes a new tool in electrophysiological investigations.